Study and personal resources of university students’ academic resilience and the relationship with positive psychological outcomes - Bagdžiūnienė, Dalia; Žukauskaitė, Irena; Bulotaitė, Laima; Sargautytė, Rūta (Frontiers in Psychology, 2025)
IntroductionEmbarking on university-level studies is a period of new challenges for young people as they meet new academic demands, environments, and teaching systems. Academic resilience, defined as students’ capacity to endure challenges while sustaining optimism, positive thinking, and emotional stability, is crucial in enabling individuals to navigate academic difficulties and foster future success. In this context, developing the role of contextual and personal factors in university students’ academic resilience and its role in predicting positive psychological outcomes is crucial. This study, grounded in the Study Demands–Resources framework, sought to examine study-related characteristics and self-efficacy as resources that support students’ academic resilience. Additionally, it aimed to explore the connections between academic resilience and positive psychological outcomes, such as student engagement and well-being.MethodThe convenience study sample included 350 students from Lithuanian universities: 79.14% were female, the mean age was 23.8 years (SD = 5.7). Students were in varying bachelor’s and master’s study programs. Data were collected using a self-administered online survey. Descriptive statistics, correlation, regression analyses, and structural equation modelling were applied for data analysis.Results and conclusionThe study found that students’ academic resilience was positively influenced by the characteristics of their study environment and self-efficacy. Furthermore, academic resilience was positively associated with student engagement and well-being. Our findings highlight the role of academic resilience in mediating the interplay between study-related resources, student engagement, and well-being. This research study features practical implications for enhancing university students’ academic resilience, engagement, and well-being by strengthening both study-related and personal resources.